Effectiveness of high‐density polyethylene container and Super Grain Bag for the storage system of cowpea grain for smallholder farmers. Issue 1 (25th November 2020) - Tivana, Lucas D.; Nguenha, Rafael J.; Viola, Paula; Monjane, Isabel; Lungu, Olipa; Kafwamfwa, Nswana
Abstract: The present study aims to evaluate the effectiveness of high‐density polyethylene container combined or not with Super Grain Bag for cowpea grain storage. The experiments were conducted on‐station and on‐farm . The storage systems tested included high‐density polyethylene container (PC), Super Grain Bag (SGB), and polypropylene bag (PB). The insect infestation level and grain damage were determined monthly for 6 months at on‐station and every 2 months for 8 months at on‐farm trials. Acceptability test of the stored grain was carried out at the end of on‐station trials with farmers. Naturally infested grain was used, with an initial infestation level of 117 insects/kg and a percentage of damaged grain of 27%. After 6 months of storage on‐station, PB resulted in an increase of insect infestation to above 1300 insects/kg of cowpea grain and an increase of damaged grain to 79%. In the SGB and PC, the number of insects increased to 573 and 364 insects/kg, while the grain damage increased to 40% and 36%, respectively. After 4 months of storage the SGB was perforated by insects, compromising its hermeticity. The combination of PC with SGB (PC + SGB) reduced the proliferation of insects and grain damage, resulting in 257 insects/kg and 34%, respectively. The farmers highly accepted grain stored at PC and PC + SGB systems. The on‐farm trials confirmed the effectiveness of the polyethylene container on limiting insects multiplication and grain damage. Thus, the polyethylene container, associated or not with Super Grain Bag, showed to be effective for storage and preservation of cowpea grain, making it suitable for smallholder farmers, thereby reducing cowpea grain losses during storage.